Решите уравнение,используя введение новой переменной (t^2-2t)^2-3=2(t^2-2t)

0 голосов
24 просмотров

Решите уравнение,используя введение новой переменной (t^2-2t)^2-3=2(t^2-2t)


Алгебра (16 баллов) | 24 просмотров
Дан 1 ответ
0 голосов

заменим (t^2-2t) на х

x^2-3=2x

x^2-2x-3=0

D=16

x=3

x=-1

 

Получим уравнения

t^2-2t=3                          и t^2-2t=-1

t^2-2t-3=0                          t^2-2t+1=0

t=3                                     D=0

t=-1                                    t= 1

 

Ответ: -1;3;1.

(753 баллов)